2013
DOI: 10.1536/ihj.54.212
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Systolic and Diastolic Function Using ECG-Gated Technetium-99m Tetrofosmin Myocardial Perfusion SPECT

Abstract: SummaryBecause left ventricular (LV) diastolic dysfunction is frequently the earliest indicator of LV dysfunction in patients with heart failure, the estimation of LV diastolic function is very important. On the other hand, electrocardiography (ECG)-gated technetium (Tc) -99m tetrofosmin single-photon emission computed tomography (SPECT) has been reported to be a useful method for evaluation of LV function. The objective of this study was to examine the usefulness of ECG-gated Tc-99m tetrofosmin SPECT in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…The mean value for PFR of hypertensive and normotensive patients in current study was higher than the mean value of PFR reported in prior studies for patients with mild diastolic dysfunction and normal study population (14,17). Akincioglu et al (17) assessed the values of diastolic function parameters in 90 patients with normal exercise gated SPECT, and no history of hypertension, diabetes, rest electrocardiogram abnormality, or known cardiac disease, and reported a mean normal value for PFR of 2.62 ± 0.46 EDV/s.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The mean value for PFR of hypertensive and normotensive patients in current study was higher than the mean value of PFR reported in prior studies for patients with mild diastolic dysfunction and normal study population (14,17). Akincioglu et al (17) assessed the values of diastolic function parameters in 90 patients with normal exercise gated SPECT, and no history of hypertension, diabetes, rest electrocardiogram abnormality, or known cardiac disease, and reported a mean normal value for PFR of 2.62 ± 0.46 EDV/s.…”
Section: Discussioncontrasting
confidence: 86%
“…Mizunobu et al (14) reported similar mean values of 1/3 MFR for patients with mild diastolic dysfunction, and patients with normal diastolic function estimated by ultrasound echocardiography (UCG) (1.01 ± 0.35 EDV/s, and 1.43 ± 0.37 EDV/s respectively). Furthermore, the 1/3 MFR of patients with mild diastolic dysfunction estimated by UCG was significantly lower than that of patients with normal diastolic function.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Beyond their capabilities to characterize myocardial architecture, perfusion, viability, and function, noninvasive imaging modalities offer the added possibility to dynamically evaluate ventricular motion during the cardiac cycle by means of ECG-gated acquisitions 1,2. Such motion characterization is achieved through sequential target detection, cavity orientation, segmentation preprocessing, and motion analysis resulting in quantitative estimates of ventricular mechanical synchrony 3…”
Section: Introductionmentioning
confidence: 99%
“…[3] Radionuclide ventriculography (RNV) has long been used in the evaluation of systolic and diastolic functions of the left ventricle, and studies correlated with echocardiography have confirmed its value. [4] Currently, however, it is used less often and does not provide information about myocardial perfusion. MPS is an ideal method with which to provide diagnostic and prognostic information about myocardial perfusion effectively and at low cost.…”
Section: Introductionmentioning
confidence: 99%